2007
DOI: 10.1530/rep-06-0304
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the mammalian membrane block to polyspermy: evidence for calcium-dependent and -independent regulation

Abstract: One crucial result of egg activation is the establishment of blocks on the zona pellucida and the egg plasma membrane to prevent fertilization by additional sperm. The mechanism(s) by which a mammalian egg regulates the establishment of the membrane block to polyspermy is largely unknown. Since Ca 2C signaling regulates several egg activation events, this study investigates how sperm-induced Ca 2C transients affect the membrane block to polyspermy, building on our previous work (Biology of ] cyt regulate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…In this case, variation in the expression of the Zp genes may account for differences in ova resistance to fertilization, offering an alternative potential mechanism for strategic adjustments in ovum defences of females reared in different social environments. The mechanism/s by which mouse ova regulate the establishment of the membrane block is largely unknown, but has been suggested to be the culmination of multiple postfertilization events that together modify the ovum's receptivity to sperm and is established in approximately the same time frame as the Zp block [61]. Certainly, responses in the cumulus oophorus, the Zp and the plasma membrane that account for plasticity in ova fertilizability need not be mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, variation in the expression of the Zp genes may account for differences in ova resistance to fertilization, offering an alternative potential mechanism for strategic adjustments in ovum defences of females reared in different social environments. The mechanism/s by which mouse ova regulate the establishment of the membrane block is largely unknown, but has been suggested to be the culmination of multiple postfertilization events that together modify the ovum's receptivity to sperm and is established in approximately the same time frame as the Zp block [61]. Certainly, responses in the cumulus oophorus, the Zp and the plasma membrane that account for plasticity in ova fertilizability need not be mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…This contact triggers a series of cellular events. First is the cortical reaction, where the cortical granules (located just beneath the egg plasma membrane surface) release enzymes that alter sperm receptors present on the surface of the vitelline layer (Gardner et al, 2007), a process vital in preventing polyspermy (Gardner et al, 2007). Another mechanism to prevent polyspermy occurs one second post-sperm/egg contact; an influx of sodium ions causes the membrane of the ovum to depolarize (Tosti and Boni, 2004).…”
Section: The Sea Urchinmentioning
confidence: 99%
“…In metazoans, a cytoplasmic Ca 21 wave is seen in the zygote immediately following sperm contact or entry, which blocks penetration by additional sperm (Runft et al, 2002;Santella et al, 2004). Studies in vertebrates, as well as echinoderms, have identified a biphasic polyspermy barrier, with a ''fast'' block at the level of the plasma membrane and a ''slow'' Ca 21 -dependent block that depends on changes to the ECM (Gardner et al, 2007;Jaffe, 1976;Wessel and Wong, 2009;Wong and Wessel, 2008). In echinoderms, as well as amphibians, the ''fast'' block results from rapid and transient membrane depolarization, whereas in mammals, the fast block is poorly defined, but appears to be independent of changes in membrane potential (Gardner et al, 2007).…”
Section: Polyspermy Barriermentioning
confidence: 99%